Neuroglobin protects offspring rats from neuronal damage induced by sevoflurane exposure to pregnant rats by inhibiting endogenous apoptosis. Issue 76 (4th June 2019) - Zhang, Yongfang; Yang, Fan; Gao, Yan; Shan, Yangyang; Dong, Yunxia; Liu, Hongtao
Abstract : As a general anesthesia drug, sevoflurane has been found to be potentially neurotoxic to the developing brain. Neuroglobin (Ngb) is a novel oxygen‐carrying globulin that has been demonstrated to have neuroprotective effects in a variety of central nervous system disorders. However, it is unclear whether Ngb has a protective effect on nerve damage caused by sevoflurane. Therefore, this study was designed to investigate the effect and related mechanisms of Ngb on neural injury induced by sevoflurane. Pregnant rats on gestational day 20 (G20) were exposed to 3.5% sevoflurane for two hours, which led to an increase of Ngb on the 0‐1st day after birth and decreased significantly on the 3rd day, while Cytochrome c increased from the 1 st day until the 7th day of offspring rats. Meanwhile, sevoflurane reduced Bcl‐2 and Hif‐1αand increased Bax and cleaved‐caspase 3 in the third day after birth. Hemin inhibits endogenous apoptosis by increasing Ngb and Hif‐1α. And increased Ngb improved the damage of long‐term learning and memory induced by sevoflurane and increased the number of neurons in the hippocampus. We concluded that Ngb can improve the neuronal injury induced by sevoflurane exposure by inhibiting apoptosis and increasing the number of neurons. And this protective effect of Ngb may be related to Hif‐1α signaling pathway. This finding may provide a novel therapeutic approach for sevoflurane ‐induced nerve damage.